The Transformation of Political Islam in Indonesia: Adapting to Modernization and Secularization - Jufri, Andi; Rosmini, Rosmini; Majid, Latifah Abdul (Jurnal Adabiyah, 2024)
Political secularization refers to a set of ideas regarded as instrumental in driving radical changes to the traditional order and the patterns of interaction between the state and religion. What was once regulated by religious-political systems has transformed into a non-sacred, pluralistic interaction, where religious dogmas previously deemed sacred have become profane. This study examines how Islam has adapted to modernization and political secularization in Indonesia. Using a descriptive qualitative research approach, it employs sociological analysis and political theory to explore this adaptation process. The findings reveal that Islam in Indonesia responds to modernization and political secularization in three distinct ways: Integration: Islam emerges as an ideological movement, using Islamic principles as central rhetoric for political activism. Acculturation: Islam positions itself as a cultural movement, maintaining political influence through cultural engagement. Agency-structuring: Islam acts both as a dialogue partner with political power and as an active agent shaping social and political structures. الملخص العلمنة السياسية هي حركة سياسية تهدف إلى غرس الاعتقاد بأن التحديث السياسي لا يمكن تحقيقه إلا إذا لعب الدين دورًا فعالًا في إحداث تغييرات جذرية في النظام التقليدي وأنماط التفاعل بين الدولة والدين. وتحولت أنماط التفاعل التي كانت تنظمها الأنظمة الدينية السياسية في السابق إلى أنماط تفاعل أكثر تعددية وغير مقدسة، حيث أصبحت العقيدة الدينية التي كانت تعتبر مقدسة في السابق، دنيوية في نهاية المطاف. يهدف هذا المقال إلى الكشف عن نمط التكيف الإسلامي مع التحديث السياسي والعلمنة في إندونيسيا. تستخدم هذه الدراسة المنهج الوصفي النوعي ذو المنهج السوسيولوجي والفكر السياسي. تظهر نتائج الدراسة أنه في الاستجابة للتحديث السياسي والعلمنة، يظهر الإسلام في إندونيسيا في ثلاثة أطياف من المواقف (التكيفات) التي تميل إلى أن تكون مختلفة. أولا، (الاندماج) يظهر الإسلام كحركة أيديولوجية من خلال جعل الإسلام لغة الحركة. ثانياً، (الثقافة)، يبدو الإسلام كحركة ثقافية، رغم أنها تركز أكثر على الجوانب الثقافية، إلا أنها لا تزال ذات محتوى سياسي. ثالثاً، (الوكالة-الهيكلة)، يظهر الإسلام كشريك في حوار السلطة، وكذلك كعامل مشارك في الهياكل الاجتماعية والسياسية. Abstrak Sekularisasi politik adalah gerakan politik yang bertujuan menanamkan keyakinan bahwa modernisasi politik yang hanya dapat tercapai jika agama berperan efektif dalam menciptakan perubahan radikal terhadap tatanan dan pola interaksi tradisional antara negara dan agama. Pola interaksi yang sebelumnya diatur oleh sistem-sistem politik-agama bertransformasi menjadi pola interaksi yang lebih pluralis dan non-sakral, di mana dogma agama yang semula dianggap sakral, akhirnya menjadi profan. Penelitian ini bertujuan untuk mengungkap bagaimana pola adaptasi Islam terhadap modernisasi dan sekularisasi politik di Indonesia. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan sosiologi dan pemikiran politik. Hasil kajian menunjukkan bahwa dalam merespons modernisasi dan sekularisasi politik, Islam di Indonesia tampil dalam tiga spektrum penyikapan (adaptasi) yang cenderung berbeda. Pertama, (integrasi), Islam tampil sebagai gerakan ideologis dengan menjadikan Islam sebagai jargon gerakannya. Kedua, (akulturasi), Islam tampil sebagai gerakan kultural, meskipun lebih berfokus pada aspek kebudayaan, tetap memiliki muatan politik. Ketiga, (strukturasi-agensi), Islam tampil sebagai mitra dialog kekuasaan, sekaligus sebagai agen yang terlibat dalam struktur sosial dan politik.